Differential effects of hemofiltration and of coupled plasma filtration adsorption on cardiac repolarization in pigs with hyperdynamic septic shock - Stengl, Milan; Sykora, Roman; Chvojka, Jiri; Krouzecky, Ales; Novak, Ivan; Varnerova, Veronika; Kuncova, Jitka; Nalos, Lukas; Sviglerova, Jitka; Matejovic, Martin (Shock (Augusta, Ga.), 2010)
The aim was to investigate effects of continuous hemofiltration (CHF) and of coupled plasma filtration adsorption (CPFA) on electrophysiological properties of the septic heart. Sepsis was induced in anesthetized pigs by fecal peritonitis and continued for 22 h either without intervention (control sepsis) or with intervention (CHF or CPFA) applied for the last 10 h of this period. Electrocardiograms were recorded at baseline, before induction of peritonitis, and 22 h later, at the end of in vivo experiment. In vitro, action potentials were recorded in right ventricular trabeculae. RR, QT, and QTc (QT corrected for heart rate) intervals were shortened by sepsis. Action potential durations (APDs) were shortened by CHF, but not by CPFA, compared with control sepsis. Continuous hemofiltration prolonged APD. Coupled plasma filtration adsorption filtrate did not exert any effect on APD. Plasma separated during CPFA prolonged APD. Continuous hemofiltration shortened cardiac repolarization, and this effect was reversed by the hemofiltrate. In contrast, neither CPFA nor the CPFA filtrate influenced APD. The data indicate that some inflammatory mediators able to delay cardiac repolarization were removed from plasma to hemofiltrate by CHF but not by CPFA.
Keywords: Hemofiltration; Swine; Animals; prasata; Electrophysiology; elektrofyziologie; zvířata; akční potenciály; septický šok; Hemodynamics; peritonitida; Action Potentials; hemodynamika; Peritonitis; Shock, Septic; hemofiltrace